Photogeneration of reactive oxygen species on uncoated silver, gold, nickel, and silicon nanoparticles and their antibacterial effects - Zhang, Wen (Langmuir : the ACS journal of surfaces and colloids, 2013)
Oxidative stress induced by reactive oxygen species (ROS) is one of the major toxicity mechanisms of engineered nanoparticles (NPs). To advance our knowledge of the photogeneration of ROS on NPs, this Letter reports the ROS generation kinetics of uncoated silver (AgNPs), gold (AuNPs), nickel (NiNPs), and silicon (SiNPs) NPs in aqueous suspension under UV irradiation (365 nm) and analyzes the potential ROS photogeneration mechanisms as well as the associated antibacterial effects. The results showed that AgNPs generated superoxide and hydroxyl radicals, whereas AuNPs, NiNPs, and SiNPs generated only singlet oxygen. The electronic structure and redox potentials of SiNPs were shown to mediate ROS generation. By contrast, ROS generation on AuNPs, AgNPs, and NiNPs was primarily due to surface plasmon resonance. The antibacterial activities of these NPs toward E. coli cells under UV irradiation were AgNPs (strongest) > SiNPs > NiNPs > AuNPs. ROS generation and metal ion release significantly enhanced the NPs' antibacterial activity